Peningkatan Prestasi Belajar Bahasa Indonesia Melalui Penerapan Model Pembelajaran Picture And Picture Siswa Kelas VI SDN 1 Kaobula - Gusli, Suhendro; Abdin, Non (Universitas Muslim Buton, 2024)
This Classroom Action Research (CAR) applies the Picture and Picture Learning Model to improve the quality of the Indonesian language learning process in the Poetry material. This model is designed so that students are more active in learning by utilizing the knowledge they already have and applying it in everyday life. With this approach, learning becomes more meaningful, because students are directly involved in the learning process through experience, not just receiving information from the teacher. The main focus of this study is to improve the quality of the learning process, not just the final result. The purpose of this CAR is to determine the extent to which the application of the Picture and Picture Learning Model can improve the learning achievement of Indonesian language in the Poetry material for grade VI students at SDN 1 Kaobula in the 2024/2025 Academic Year. This research was conducted in two cycles. The results of the study showed an increase in student learning completeness classically, from 65% in cycle I to 80% in cycle II. In addition, the average student evaluation score increased significantly. From the aspect of learning activities, the average score increased from 3.2 (Quite Active category) in cycle I to 4.1 (Active category) in cycle II, indicating an increase of 9%. This proves that the implementation of the Picture and Picture Learning Model can improve both student activity and learning achievement effectively. Keywords: Picture and Picture Learning Model, Poetry